Pragmatic Discourse of Givenness through A-Movement Constructions of Thai EFL Learners - Wongkittiporn, Abhinan (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2024)
The current study examined Thai EFL Mattayom learners’ pragmatic discourse of givenness via A-movement constructions. While previous studies focused on Thai undergraduate students and their error production in passive voice, this study innovatively contributes to the field by selecting a different group of participants. The participants in this study were 67 Mattayom students in Thailand, of which 45 were from public schools and 22 were from private schools. The participants were asked to write an academic essay on the topic of Thai Soft Power, which is the Thai government's campaign for tourism and culture from 2023 to 2024. The data analysis follows the principle of pragmatic discourse of givenness. The SPSS version 29 was used for the data analysis to seek a correlation between the production of passive voice by EFL learners and pragmatic discourse of givenness via A-movement constructions. The study showed that there is no statistically significant relationship between the production of passive voice by EFL Mattayom learners and pragmatic discourse of givenness where the p-value is reported at 0.79. It seems that Thai EFL Mattayom learners have not yet acquired the pragmatic discourse of given and new information in producing A-movement constructions in English. The discussion is given in the scope of a lack of experience of writing passive voice with other discourses. In addition, the traditional styles of teaching active and passive voice as interchangeable structures in Thai schools do not support the actual use of A-movement constructions in practicality. It is recommended that pragmatic discourse of givenness via A-movement constructions should be built into the curriculum for Thai EFL learners to develop cohesion in writing academic texts.